Of all people, by all people, for all people? Perceptions of economic inequality and democracy in Africa - Isbell, Thomas Alexander (Department of Political Studies, 2022)
In this thesis I explore whether perceptions of individual economic inequality are linked to the legitimacy of democracy in Africa. Past research has suggested that high levels of economic inequality may affect the legitimacy of democracy, by reducing support for democracy and discouraging political participation. However, these findings have largely been described for cases in the global North. Little evidence is available for cases in Africa. This reflects an important omission in the literature. Africa – as a region – is simultaneously characterized by some of the highest levels of economic inequality in the world, and many democracies retain autocratic elements non-fully consolidated hybrid-regimes. This thesis addresses this omission. Much of the existing research on the consequences of economic inequality uses country-level measures of economic inequality, such as the Gini coefficient or the Palma ratio. This is problematic for two reasons. First, a growing body of research suggests that ordinary people widely misjudge levels of economic inequality and that people's perceptions of economic inequality are often weakly associated with actual, objective, levels of economic inequality. At an individual level people's attitudes and behaviours are thus probably informed by their perceptions of economic inequality rather than objective levels of economic inequality. Second, high-quality comparative data on economic inequality are predominantly only available for a limited number of economically developed countries. For countries in Africa, such data are often of poor quality, only available in irregular intervals and not easily comparable. This limits the empirical analysis of such cases. I bridge both problems by using representative survey data collected in 34 countries between 2016 and 2018 by the Afrobarometer value-survey (n>45000). Specifically, I compute measures of perceptions of individual economic inequality by using a survey question which asks respondents whether they feel relatively deprived (in regard to their living situation), relatively advantaged or equal to other people in their country. To link perceptions of individual economic inequality with democratic legitimacy, I apply Norris' 2011 multi-dimensional conceptualization of ‘political support'. Following Norris' conceptualization, I structure my thesis as a series of analyses focusing on the relationship between perceptions of individual inequality and the various dimensions of political support – support for democracy as a regime, satisfaction with how democracy is working, and trust in state institutions and representative government institutions. Lasty – as the legitimacy of democracy is reflected not only in people's attitudes towards and evaluations of democracy, but also in their actions – I explore whether perceptions of individual economic inequality are linked to civic and political participation. Employing multi-level analyses, I find that that people who feel equal to others are more supportive of democracy and have more demand for democracy than people who do not feel equal to others. Conversely, my results show that both those feeling severely relatively deprived and those feeling severely relatively advantaged tend to be less supportive of democracy and have less demand for democracy. Feeling relatively advantaged is significantly associated with more positive evaluations of how democracy is working in the respondent's country, while feeling relatively deprived is significantly associated with less positive evaluations. These results suggest that rather than emphasizing equality, people's expectations of the functioning of democracy in practice are driven by egocentric considerations. Likewise, people display egocentric motives regarding how much they trust representative government institutions and state institutions. I find that perceptions of individual relative deprivation are significantly associated with less political trust and that perceptions of relative advantage are significantly associated with more political trust. For all models, I find that the effect of perceptions of individual economic inequality remain significant, even when controlling for the effects of widely used explanations in the literature, such as partisanship, economic performance evaluations and perceptions of corruption. This indicates that how people feel compared to other people is an important explanation of how supportive people are of democracy, how they evaluate the functioning of democracy and how much they trust political leaders and state institutions. Lastly, I find that being materially poor and feeling relatively deprived do not appear to be consistently linked to being ‘voiceless' or ‘resigned' as the developmental narrative may suggest. The results show that people who feel relatively deprived are more likely to engage in communing activities, irrespective of poverty experience, but less likely to contact representatives when absolute lived poverty experience is considered. The models moreover suggest that people who have experienced more poverty are more engaged in communal activity, more likely to protest and more likely to contact representatives. Both perceptions of relative deprivation and experiences of poverty appear unrelated to voting. Overall, this thesis provides a number of important contributions to areas of both democracy research and economic research that have been understudied in the past. The results suggest that perceptions of individual economic inequality across 34 African countries consistently correlate with people's attitudes towards and evaluations of democracy, their trust in political leaders and institutions, and their levels of civic and political participation. This tells us that how people feel compared to others matters in terms of the legitimacy of democratic regimes in Africa. In many cases the results suggest that perceptions of relative deprivation and perceptions of relative advantage do not simply work in opposite ways. Much emphasis in both the public discourse and the empirical literature has been placed on the role of being or feeling relatively deprived. The results in this thesis clearly demonstrate that those who feel relatively better off are of equal importance and need to be studied in the future. Moreover, this thesis contributes to the methodological literature by providing a novel approach to the study of the consequences of economic inequality in Africa by focusing on perceptions and the use of value-survey data. Especially in the context of Africa (and the wider developing world) where high-quality macro-level data are often limited, the use of value-survey based experiential measures of inequality may open manifold new avenues of enquiry in a diverse set of fields of research.